2008
DOI: 10.1021/es801082a
|View full text |Cite
|
Sign up to set email alerts
|

Key Amino Acids in the Aryl Hydrocarbon Receptor Predict Dioxin Sensitivity in Avian Species

Abstract: Dioxin-like compounds are toxic to most vertebrates, but significant differences in sensitivity exist among species. A recent study suggests that the amino acid residues corresponding to Ile324 and Ser380 in the chicken aryl hydrocarbon receptor 1 (AHR1) are important determinants of differential biochemical responses to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in chickens and common terns. Here, we investigate whether the identity of these amino acid residues can predict embryonic sensitivity to dioxin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(196 citation statements)
references
References 38 publications
(43 reference statements)
8
187
1
Order By: Relevance
“…However, despite the aryl hydrocarbon receptor (AhR) activity and TEQ of PCB 77, no adverse effects had been observed on embryonic survival in treated or environmentally exposed tree swallows. This lack of lethality may be ascribed to interspecific differences of PCB congeners on the activation of the AhR; according to these data, tree swallows have lower sensitivity to PCBs than other avian species [5,7,8,40]. Similarly, the potency of dioxin-like PCBs with similar chemical structures to dioxins (e.g., 2,3,7,8-tetrachlorodibenzodioxin) is toxicologically categorized by TEFs [41,42].…”
Section: Exposure To Pcb 77 Did Not Affect Survivabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…However, despite the aryl hydrocarbon receptor (AhR) activity and TEQ of PCB 77, no adverse effects had been observed on embryonic survival in treated or environmentally exposed tree swallows. This lack of lethality may be ascribed to interspecific differences of PCB congeners on the activation of the AhR; according to these data, tree swallows have lower sensitivity to PCBs than other avian species [5,7,8,40]. Similarly, the potency of dioxin-like PCBs with similar chemical structures to dioxins (e.g., 2,3,7,8-tetrachlorodibenzodioxin) is toxicologically categorized by TEFs [41,42].…”
Section: Exposure To Pcb 77 Did Not Affect Survivabilitymentioning
confidence: 97%
“…Avian species are variable in their sensitivity to PCB congeners, but it has been well established that coplanar dioxin-like congeners such as PCBs 77, 81, and 126 induce toxicity at higher rates than non-dioxin-like congeners [4][5][6][7][8]. Recent contaminant analysis has shown that concentrations of PCBs 77, 81, and 126 account for approximately 86, 9, and 3% respectively, of the total PCB toxic equivalents (TEQs) in tree swallow eggs collected along the Upper Hudson River in 2004 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Given the nodal position of AHR in a regulatory network and the necessity and sufficiency of AHR activation for dioxin toxicity, AHR activation offers a large mutational target of the sort that tends to be preferred targets for repeated evolution [28]. Molecular variants in the AHR gene are associated with dioxin tolerance in birds [29], mammals [30] and fishes [31]. Rats that carry a mutation in the AHR transactivation domain are relatively dioxinresistant, though only a subset of the AHR transcriptional targets is refractory to dioxin induction [32].…”
mentioning
confidence: 99%
“…In chicken embryos exposed from the beginning to the end of incubation (as in the present field study), thymic and bursal atrophy have been observed over a dose range of approximately 13 to 80 pg TEQs/g egg (converting from PCB concentrations to TEQs using World Health Organization toxic equivalency factors) [18][19][20]. As a species, herring gulls are approximately 33 to 50 times less sensitive to 2,3,7,8-TCDD compared to chickens, and 7-to 200-fold less sensitive to other planar PCDDs, PCDFs, and PCBs [39,40]. Still, some individual gulls are as sensitive as the average chicken [39].…”
Section: And 3) (Teqs For the Great Lakes And New Yorkmentioning
confidence: 99%